2012
DOI: 10.1017/s0144686x12000517
|View full text |Cite
|
Sign up to set email alerts
|

Transport resources, mobility and unmet transport needs in old age

Abstract: Previous research has shown that mobility and the ability to leave the home are among the essential aspects of older people's quality of life. However, surveys of older people's access to transport resources and the impact of mobility on welfare and wellbeing are few. Many previous studies are based on small samples or qualitative data. The questions addressed in this paper are how transport resources are distributed among different groups of older people, to which degree the transport needs of these groups ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 28 publications
(32 reference statements)
7
96
0
2
Order By: Relevance
“…With regard to met and unmet activities, results are less clear: Haustein (2012) showed that car availability was related to the number of leisure activities even when controlling for relevant background variables, while this was not the case in a study by Scheiner (2006), who additionally found no significant relation to the existence of unmet leisure needs or to leisure satisfaction. By contrast, two more recent studies demonstrated a significant effect of not having a driving licence or a car on unfulfilled mobility needs, though controlling for similar factors as did Scheiner Hjorthol, 2013). Differences may be partly explained by different levels of car dependency in the study areas, which makes the car more or less essential for fulfilling older people's mobility needs.…”
Section: Car Accessmentioning
confidence: 64%
See 4 more Smart Citations
“…With regard to met and unmet activities, results are less clear: Haustein (2012) showed that car availability was related to the number of leisure activities even when controlling for relevant background variables, while this was not the case in a study by Scheiner (2006), who additionally found no significant relation to the existence of unmet leisure needs or to leisure satisfaction. By contrast, two more recent studies demonstrated a significant effect of not having a driving licence or a car on unfulfilled mobility needs, though controlling for similar factors as did Scheiner Hjorthol, 2013). Differences may be partly explained by different levels of car dependency in the study areas, which makes the car more or less essential for fulfilling older people's mobility needs.…”
Section: Car Accessmentioning
confidence: 64%
“…This has been interpreted as indicating a gender-related disadvantage in mobility, which is further supported by findings showing that older women depend more on others for their personal travel needs (Siren & Hakamies-Blomqvist, 2006), are more affected by loss of a spouse with regard to unfulfilled travel needs (Ahern & Hine, 2012) and experience more unmet travel needs than men (Hjorthol, 2013;Scheiner, 2006;.…”
Section: Gendermentioning
confidence: 86%
See 3 more Smart Citations